Assessment of the Relationship between Mortality and Troponin I Levels in Hospitalized Patients with the Novel Coronavirus (COVID-19) - Sinem Özyılmaz; Esra Ergün Alış; Emrah Ermiş; Samir Allahverdiyev; Hakan Uçar (Medicina, 2020)
Background and Objectives: This study aimed to evaluate the relationship between mortality and cardiac laboratory findings in patients who were hospitalized after a positive PCR for COVID-19 infection. Materials and Methods: This study included patients who were admitted to or referred to the hospital between 20 March and 20 June 2020, diagnosed with COVID-19 via a positive RT-PCR from nasal and pharyngeal swab samples. The troponin I level was measured from each patient. Medical records of patients were retrospectively reviewed and analyzed. Results: A hundred and five patients who were diagnosed with COVID-19 and hospitalized, or who died in the hospital due to COVID-19, were included in this study. There was a statistically significant difference between the troponin I high and low level groups in terms of age (years), BMI, shortness of breath (SB), oxygen saturation (%), hypertension, length of stay in the ICU; and for mortality, C-reactive protein, the neutrophil-to-lymphocyte ratio, hemoglobin, lactate dehydrogenase, ferritin, D-dimer, creatine kinase-MB, prothrombin time, calcium, and 25-hydroxy vitamin 25(OH)D3 (all p < 0.05). In the logistic analyses, a significant association was noted between troponin I and the adjusted risk of mortality. A ROC curve analysis identified troponin I values > 7.8 pg/mL as an effective cut-off point in mortality for patients with COVID-19. A troponin I value of higher than 7.8 pg/mL yielded a sensitivity of 78% and a specificity of 86%. Conclusions: The hospital mortality rate was higher among patients diagnosed with COVID-19 accompanied by troponin levels higher than 7.8 pg/mL. Therefore, in patients diagnosed with COVID-19, elevated troponin I levels >7.8 pg/mL can be considered an independent risk factor for mortality.